2002
DOI: 10.1046/j.1439-0272.2002.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and function of FSH receptor genetic variants in normal men

Abstract: Follicle stimulating hormone (FSH) plays a key role in the maintenance of qualitatively and quantitatively normal spermatogenesis. It controls gamete development through Sertoli cells, via binding to its receptor. The influence and importance of FSH receptor (FSHR) variants on Sertoli cell function is not completely understood and remains to be investigated. In this retrospective study, we explored the impact and action of two distinct FSHR isoforms, Thr307/Asn680 and Ala307/Ser680, in a large group of men. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 23 publications
(27 reference statements)
4
29
1
Order By: Relevance
“…Since the FSHR genotype is responsible for some differences in the FSH dose needed for stimulation in women [19,38] and in transcriptional activity in vitro [114], several studies have been conducted to verify possible differences in men. However, the common FSHR polymorphism Asn680Ser showed no effect on serum FSH levels and other clinical parameters in men [18,115], leading to a discrepancy between the two genders which still remains unexplained. In men, several investigations on the distribution of G-29A, A919G and A2039G FSHR SNPs were made, producing various and sometimes contradictory results [18,[116][117][118] and suggesting that some polymorphisms lead to testicular dysfunction only when in association with a particular genetic background or environmental factors.…”
Section: The Fshr Polymorphisms In Male Fertilitymentioning
confidence: 98%
“…Since the FSHR genotype is responsible for some differences in the FSH dose needed for stimulation in women [19,38] and in transcriptional activity in vitro [114], several studies have been conducted to verify possible differences in men. However, the common FSHR polymorphism Asn680Ser showed no effect on serum FSH levels and other clinical parameters in men [18,115], leading to a discrepancy between the two genders which still remains unexplained. In men, several investigations on the distribution of G-29A, A919G and A2039G FSHR SNPs were made, producing various and sometimes contradictory results [18,[116][117][118] and suggesting that some polymorphisms lead to testicular dysfunction only when in association with a particular genetic background or environmental factors.…”
Section: The Fshr Polymorphisms In Male Fertilitymentioning
confidence: 98%
“…The genotype distribution of the polymorphism in position 680 differs according to ethnicity so that the homozygous Ser680 genotype is more uncommon in Asia than among Europeans, whereas the homozygous Asn680 genotype is clearly over-represented in Asian populations [8]. Two uncommon allelic combinations, Thr307/Ser680 and Ala307/Asn680, are present in less than 5% of populations of European and Asian origin [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The allelic variants of the FSHR have been reported to be similarly distributed in fertile and infertile men [14][15][16], and no differences in sperm and testicular parameters were noted between fertile controls and infertile men, subdivided according to FSHR genotype [6,9,17,18]. In contrast, some studies have shown differences in the FSHR genotype distribution among fertile controls and infertile men [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations, however, found significant variations of SNP distributions, and suggested that ethnic differences could be involved in polymorphism-related infertility [29]- [32]. In some previous studies, the G-29-A919-A2039 haplotype was shown to be more prevalent in normozoospermic men than in azoospermic patients (38.4% vs. 33.9%, respectively; chi (2) test, P = 0.045), indicating that this haplotype may be a protective factor against male sterility [33].…”
Section: Discussionmentioning
confidence: 98%